2019
DOI: 10.4236/jep.2019.1011085
|View full text |Cite
|
Sign up to set email alerts
|

Physico-Chemical Characterization of Waters and Sediments of Basins in the Cotton Area in Benin: Case of the Alibori Basin in the Commune of Banikoara North of Benin

Abstract: The Alibori Basin, with an area of 13,400 km 2 , is a tributary of the Niger River in Benin. It is a river that passes through the potentially agricultural area of Benin. The waters of the river are useful for wildlife and are used for various purposes (drinking water, laundry, domestic activities). They regularly receive the discharges and drainage of the residues of the chemical fertilizers and pesticides not used by crops during the cultivation of the river and watershed bank. This study aims to assess the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 13 publications
(8 reference statements)
1
5
0
Order By: Relevance
“…Zinc, copper and lead were more concentrated in the sediments during the rainy season, which is a cultivation period, than the dry season, unlike cadmium. This observation is in agreement with Chitou et al (2019) who reported similar variation for TMEs concentrations in Alibori River's sediments between the dry season and the rainy season in 2018.In accordance with Chitou et al (2019), it could be concluded that the high values of TME during the cultivation period were due to the use of fertilizers and pesticides since the river is located in a rural area dominated by agricultural activities (Chitou et al, 2019). The concentration of Zinc and copper in the sediments has increased compared to that obtained in the 2018 during the dry season (Max: 15.6 mg.kg-1 for zinc, 19.1 for copper) and the rainy season (Max: 175 mg.kg -1 for zinc, 231 mg.kg -1 for copper) using a metalyser (Chitou et al, 2019).…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Zinc, copper and lead were more concentrated in the sediments during the rainy season, which is a cultivation period, than the dry season, unlike cadmium. This observation is in agreement with Chitou et al (2019) who reported similar variation for TMEs concentrations in Alibori River's sediments between the dry season and the rainy season in 2018.In accordance with Chitou et al (2019), it could be concluded that the high values of TME during the cultivation period were due to the use of fertilizers and pesticides since the river is located in a rural area dominated by agricultural activities (Chitou et al, 2019). The concentration of Zinc and copper in the sediments has increased compared to that obtained in the 2018 during the dry season (Max: 15.6 mg.kg-1 for zinc, 19.1 for copper) and the rainy season (Max: 175 mg.kg -1 for zinc, 231 mg.kg -1 for copper) using a metalyser (Chitou et al, 2019).…”
Section: Discussionsupporting
confidence: 93%
“…However, the pH being inversely proportional to the temperature, therefore the decrease in pH suggest to the increase in temperature of the medium, thus causing the decrease in the absorption of copper and zinc. There was likely a phenomenon of chemical release as shown in reaction Scheme 2, which explains the increase in the concentrations of the latter (TME) observed in the water in previous work in this period (Chitou et al, 2019). There is a great affinity between organic matter and metallic trace elements (Zhao et al, 2012), which explain the strong correlation observed between the oxidizable fraction of copper, zinc and organic matter during the rainy season as shown by the circle of correlation.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations